Medical Scholarships Linked to Mandatory Service: The Nepal Experience - Mahat, Agya; Zimmerman, Mark; Shakya, Rabina; Gerzoff, Robert B. (Frontiers in Public Health, 2020)
Introduction: Nepal has one of the world's lowest physician to population ratios, with a critical shortage of rural physicians. The Nepal Government uses the private sector to address this shortage of rural physicians. All private medical colleges must offer total scholarships, free of cost, to a proportion of their annual MBBS student intake. These scholarships come with a compulsory two-year service contract, which must be completed at public hospitals post-graduation. The mandatory service requirement was implemented in 2005/2006 and this paper evaluates the first decade of this scholarship program, with particular attention to the mandatory service requirement. Methods: We collected data on MBBS scholarship awardees from the Scholarship Section at the Ministry of Education, Department of Health Services, and the Ministry of Health and evaluated trends, service completion, and location. Results: Initially, because of poor monitoring, the mandatory service completion rate was low. Rates increased to 74–98% when strict rules tied service completion certificates to obtaining medical registration. In the past 4 years, three cohorts of scholarship doctors who completed their service requirements served 78% of their service-days in rural hospitals (primary healthcare centers and district hospitals). Yet, geographic inequities in physician distribution persist. Only 51% of district hospitals had at least one scholarship doctor, 31% of the district hospitals had more than 1.5 scholarship doctors, while 7% had none. The district hospitals in the Central region, which includes the capital city, had twice the number of scholarship doctors compared to the Mid-western region, which includes some of the country's most remote areas. Conclusion: The scholarship program has partially succeeded in reducing the physician shortage in Nepal's rural hospitals. To address the remaining inequities in physician distribution, efficient management systems, appropriate medical training, and support for rural practice are vital.